WIC staff and healthcare professional perceptions of an EHR intervention to facilitate referrals to and improve communication and coordination with WIC: A qualitative study - Abigail McCall; Ashley E. Strahley; Katy W. Martin-Fernandez; Kristina H. Lewis; Angelina Pack; Beatriz Ospino-Sanchez; Ivy Greene; Gabriela de la Vega; Alysha J. Taxter; Sally G. Eagleton; Kimberly G. Montez (Journal of Clinical and Translational Science, 2024)
Abstract